STRESS AND LIFE SATISFACTION AMONG ALCOHOL ADDICTS - Stevan Barać,; Vukčević, Branimir; Gutić, Medo; Đorđić, Milan; Safiye, Teodora (Medicinski časopis, 2022)
Objective. The aim of the study was to determine the level of stress and life satisfaction in alcohol addicts, ie to examine whether respondents diagnosed with alcohol dependence (F10.2) differ according to the level of stress and life satisfaction in relation to respondents from the general population.Methods. The research was designed as a non-experimental, observational cross-sectional study, and was conducted in the period from January to July 2021, at the University Clinical Center Kragujevac. The sample consisted of 80 subjects of both sexes, aged 22 to 36 years, divided into two groups: the clinical group (subjects diagnosed with alcohol dependence - F10.2) and the control group of subjects without psychiatric illness.Results. Study has shown that alcohol addicts have clinically significant and severe symptoms of stress, that stress symptoms were positively correlated with alcoholism, and negative with life satisfaction. In our sample, the association between stress and life satisfaction in addicts was very negative and very significant (ρ = - 0.645, p
Keywords: stress, life satisfaction, alcohol dependence